Impact of Mastering Traditional Characters to Learn Simplified Characters – In Analogy Simplified Picto-Phonogram Characters As Reference - Lim, Sugiato (Bina Nusantara University, 2014)
There are a number of Southeast Asian students begin to learn Chinese in their own country based on traditional Chinese characters. Therefore, author based on own learning experience talked about the influence of mastering traditional characters to learn simplified Chinese characters. By collecting the traditionalcharacter texts, summarizing the occurrence of error categories of simplified Chinese characters, and based on the Chinese character simplification methods in “Fan Jian Zi Duizhao Zidian”, research summed up the difficulties in learning Chinese simplified characters. This study was mainly based on the analogy simplified characters as the breakthrough point. The first part of this article introduces the classification of pictophonogram characters in simplified. The second part of the article introduces the impact of learning simplifiedChinese characters while learners get traditional characters background. The last part, article draws the conclusion that the impact of mastering traditional characters to learn simplified Chinese characters might be a double-edged sword. The proper understanding is helpful to the study of simplified characters, grasp the inappropriate is likely to mislead the learner.